Produksi Hasil Inovasi Pengembangan Produk Jagung untuk Meningkatkan Pendapatan Masyarakat Nagari Kinali, Pasaman Barat - Yasri Yasri; Anni Faridah; Wirnelis Syarif; Astra Prima Budiarti (Universitas Negeri Padang, 2020)
The problem faced by communities in Nagari Kinali, Pasaman Barat is the low level of education so that it is difficult to get the decent income. The purpose of this activity is to increase community's income, create jobs and increase the price of corn at the farm level by developing products and innovation for the corn commodity. The method stages in this activity include training and coaching to improve product quality. For this reason, interviews were conducted so that those selected were people who had high motivation to be trained to make products. Housewives in the BUMNag Ganto Kinali region are trained and nurtured until they succeed in making quality products.